Pathogen-Associated Molecular Patterns Induced Crosstalk between Dendritic Cells, T Helper Cells, and Natural Killer Helper Cells Can Improve Dendritic Cell Vaccination - Tammy Oth; Joris Vanderlocht; Catharina H. M. J. Van Elssen; Gerard M. J. Bos; Wilfred T. V. Germeraad (Mediators of Inflammation)
A coordinated cellular interplay is of crucial importance in both host defense against pathogens and malignantly transformed cells. The various interactions of Dendritic Cells (DC), Natural Killer (NK) cells, and T helper (Th) cells can be influenced by a variety of pathogen-associated molecular patterns (PAMPs) and will lead to enhanced CD8+ effector T cell responses. Specific Pattern Recognition Receptor (PRR) triggering during maturation enables DC to enhance Th1 as well as NK helper cell responses. This effect is correlated with the amount of IL-12p70 released by DC. Activated NK cells are able to amplify the proinflammatory cytokine profile of DC via the release of IFN-γ. The knowledge on how PAMP recognition can modulate the DC is of importance for the design and definition of appropriate therapeutic cancer vaccines. In this review we will discuss the potential role of specific PAMP-matured DC in optimizing therapeutic DC-based vaccines, as some of these DC are efficiently activating Th1, NK cells, and cytotoxic T cells. Moreover, to optimize these vaccines, also the inhibitory effects of tumor-derived suppressive factors, for example, on the NK-DC crosstalk, should be taken into account. Finally, the suppressive role of the tumor microenvironment in vaccination efficacy and some proposals to overcome this by using combination therapies will be described.